Amina the Milkmaid - Pam, Fatima (Longman Nigeria Plc, 1988)
This is the story of a milkmaid who becomes a princess. Amina is kidnapped on her way to the market one day and sold off to a very powerful king in a distant land. The king's son Ahmed falls in love with her. They get married and live happily ever after.
Keywords: Juvenile literature-Fiction-Nigeria (English)